2015
DOI: 10.3171/2014.10.spine1496
|View full text |Cite
|
Sign up to set email alerts
|

Main thoracic curve adolescent idiopathic scoliosis: association of higher rod stiffness and concave-side pedicle screw density with improvement in sagittal thoracic kyphosis restoration

Abstract: OBJECT The aim of this study was to evaluate the effects of rod stiffness and implant density on coronal and sagittal plane correction in patients with main thoracic curve adolescent idiopathic scoliosis (AIS). METHODS The authors conducted a retrospective study of 77 consecutive cases involving 56 female and 21 male patients with Lenke Type 1 main thoracic curve AIS who underwent single-stage posterior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 44 publications
(66 reference statements)
1
38
2
Order By: Relevance
“…However, the effect of implant density on sagittal plane correction and TK restoration has been reported in only a few studies, and the results have been controversial [12,14,19]. Larson et al [12] demonstrated that decreased TK was correlated with increased screw density for Lenke type 1 and 2 curves.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the effect of implant density on sagittal plane correction and TK restoration has been reported in only a few studies, and the results have been controversial [12,14,19]. Larson et al [12] demonstrated that decreased TK was correlated with increased screw density for Lenke type 1 and 2 curves.…”
Section: Discussionmentioning
confidence: 99%
“…Larson et al [12] demonstrated that decreased TK was correlated with increased screw density for Lenke type 1 and 2 curves. Conversely, Liu et al [14] documented that higher screw density provided better TK restoration than low screw density. Recently, Sudo et al [9] also documented that in patients with preoperative TK < 15°, a significant positive correlation was found between the change in TK and screw density, whereas no correlation was found in patients with TK ≥15°, suggesting that screw density had a positive effect on TK restoration in patients with hypokyphotic thoracic spines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bharucha et al explained that most of the cases in the LD group were their earlier cases, with the latter cases having an HD screw pattern, and increasing experience with implanting pedicle screws led to a decreased operative time. Finally, the data from the study by Liu et al 20 were divided into 2 subgroups according to the diameter of the titanium rods: low stiffness (5.5 mm) and high stiffness (6.35 mm).…”
Section: Data Extractionmentioning
confidence: 99%
“…In addition, high-density (HD) screw constructs have been shown to result in better restoration of thoracic kyphosis and better spinal appearance questionnaire (SAQ) scores. 12,20,28 However, a large body of research has shown that low-density (LD) screw constructs can provide similar radiographic or clinical outcomes. 3,7,[22][23][24][25]30,33 Furthermore, the number of pedicle screws placed has been shown to be an independent predictor of increased total cost for patients undergoing AIS correction procedures.…”
mentioning
confidence: 99%